EFEKTIVITAS EMAS (ECONOMIC MATERNITY SIMULATOR) TERHADAP PENINGKATAN SKILL PEMERIKSAAN KEHAMILAN MAHASISWA KEBIDANAN UNIVERSITAS MUHAMMADIYAH SURABAYA - Nova Elok Mardliyana; Irma Maya Puspita; Nur Hidayatul Ainiyah (JOMIS (Journal of Midwifery Science), 2022)
Antenatal care is one of the health services provided by midwives to monitor the health welfare of the mother and fetus. One of the competencies possessed by a midwife is to provide obstetric care for pregnancy which includes history taking, physical examination, laboratory, and counseling. The limited learning media for pregnancy phantom can make students less understanding of pregnancy examinations. For this reason, researchers made an innovative EMAS (Economic Maternity Simulator) learning media. This research is a type of quantitative research. The method used is an experimental research method with a quasi experimental research design. In this design the treatment and control groups were not randomly selected. Data analysis used Non-paired T-Test. The results of the study, it was found that there was a difference in the average score of prenatal care skills before and after using EMAS of 3.30 with a p value of 0.011 (p <0.05), 95% CI 0744-5.907. Statistically there is a significant difference and it can be concluded that EMAS has an effect on improving prenatal examination practicum skills.